UJI KONSENTRASI EKSTRAK DAUN MIMBA (Azadirachta indica A. Juss) TERHADAP MORTALITAS ULAT BAWANG Spodoptera exigua Hubner. DI LABORATORIUM - Desita Salbiah; Muhammad Tawi (DINAMIKA PERTANIAN, 2025)
Spodoptera exigua is a pest that poses a major problem for farmers because it can reduce crop yields and cause significant damage to shallot crops. Infestation by S. exigua can result in yield losses of 34–54% in shallot plants. Neem leaf botanical insecticide (Azadirachta indica A. Juss.) can be used as a safe alternative for controlling S. exigua. This study aimed to determine the effective concentration of neem leaf extract against the mortality of the beet armyworm pest, Spodoptera exigua Hübner, in the laboratory. The study was conducted at the Plant Pest Laboratory, Faculty of Agriculture, University of Riau, from March to May 2024, using a Completely Randomized Design (CRD) with six treatments and four replications. The treatment applications consisted of neem leaf extract concentrations of 0 g·l⁻¹ water, 20 g·l⁻¹ water, 40 g·l⁻¹ water, 60 g·l⁻¹ water, 80 g·l⁻¹ water, and 100 g·l⁻¹ water. The results showed that the most effective concentration for controlling S. exigua was 60 g·l⁻¹ of neem leaf powder extract, which resulted in a total mortality rate of 80%, with the onset of death occurring 18 hours after application.